Ethylene related ripening of 'SunGold™' kiwifruit : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand. EMBARGOED until 15 June 2031. - Tongonya, Jeritah (Massey University, 2020)
A key component of the success of the New Zealand kiwifruit industry is the consistent provision of high-quality produce. The projected increase in kiwifruit volumes necessitates the widening of harvest and marketing windows. Two different kiwifruit export marketing strategies are currently deployed: i) Early season fruit are delivered for immediate sale (‘KiwiStart’), ii) later season fruit have a maturity that enables extended postharvest cool storage (‘MainPack’). These marketing strategies determine harvest criteria and subsequent postharvest management practices employed in the supply cool chain. The introduction of new cultivars, e.g. ‘SunGold™’, necessitates a re-evaluation of the postharvest ripening and storage practices, tuning the requirements to the specific responses of each cultivar. Since there is minimal information on ethylene related responses for ‘SunGold™’, research to develop a fundamental understanding of these responses is crucial for optimal management and performance of the product in the market. The purpose of this PhD is to determine the effect of industry-relevant ethylene concentrations on ‘SunGold™’ quality progression (firmness and soluble solids content (SSC)). With that understanding, a semi-mechanistic model for the simultaneous description of firmness decline and soluble solids increase under dynamic temperature conditions and ethylene concentrations was developed.--Shortened abstract
Embargoed until 15 June 2031
Keywords: Kiwifruit; Ripening; Mathematical models; Storage; Postharvest technology; Ethylene; Physiological effect; 300806 Post harvest horticultural technologies (incl. transportation and storage)